2015
DOI: 10.9734/bmrj/2015/18169
|View full text |Cite
|
Sign up to set email alerts
|

Ring Worm Skin Infection in a Rural Community of Bushenyi (Uganda)

Abstract: Aim: Ring worm skin infections which have continuously been neglected in several communities of sub Saharan Africa, thus leading to the development of herbal remedies as communities seek to find solutions to the menace. The aim of this study was to assess the community skin ring worm Short Research Article

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Literatures have shown that fungal infections of the skin and scalp (dermatophytosis) represent a relatively common problem especially in the tropical and subtropical regions of the world where warm and humid climate provides a favourable environment for fungi [5, 2426]. They have become a significant health problem affecting children, adolescents, and adults [27–29].…”
Section: Discussionmentioning
confidence: 99%
“…Literatures have shown that fungal infections of the skin and scalp (dermatophytosis) represent a relatively common problem especially in the tropical and subtropical regions of the world where warm and humid climate provides a favourable environment for fungi [5, 2426]. They have become a significant health problem affecting children, adolescents, and adults [27–29].…”
Section: Discussionmentioning
confidence: 99%